Sistem Rekomendasi Pemilihan Mobil Menggunakan Metode EDAS - ariadi, hastomo; Zuliarso, Eri (Jurnal Teknik Elektro dan Komputasi (ELKOM), 2020)
According to data from the Indonesian Automotive Industry Association, or GAIKINDO, car sales decreased in 2020 and 2021 as a result of the Covid-19 epidemic, but increased by 49% in 2022 and 2023. This demonstrates that, when it comes to personal transportation, cars are preferred by Indonesians over alternative options. In order to choose automobiles based on the brand, model, type, price, engine capacity, transmission, year of manufacture, and gasoline capacity, this research will employ the EDAS approach. A Honda CRV automobile with a value of ASi = 0,812 was the recommendation that emerged from the selection criteria for the Honda brand and CVT gearbox, and a Honda Brio car whit a value of ASi = 0,713 was the second recommedation and a Honda BRV with a value of ASi = 0,6888 was the thrid recommendation.